Monitoring temporal changes of seismic properties - Aoki, Yosuke (Frontiers in Earth Science, 2015)
Temporal changes of seismic properties, such as velocity, attenuation, anisotropy, and scattering properties, have been inferred by active methods for decades and more recently by passive methods. In particular, passive methods are capable of monitoring seismic properties because they do not require earthquakes but rely on continuously excited signals in the ocean, for example, a collection of continuous monitoring of seismic velocities has revealed that the susceptibility of velocity changes to stress perturbations are highly variable. These variations can be translated to variability of third-order elastic moduli, elastic moduli arising by considering finite deformation. The third-order elastic moduli are shown by theoretical studies to be a good indicator of granular properties of rocks and, in general, as to how fluids interact with solid rocks. Advancement of theoretical and observational studies will gain more insights into the nature of third-order elastic moduli, which will eventually become yet another parameters to characterize the properties of rocks.